Photolysis for the Removal and Transformation of Pesticide Residues During Food Processing: A State-of-the-Art Minireview - Xiao, Qian; Xuan, Xiaoxu; Boczkaj, Grzegorz; Yoon, Joon Yong; Sun, Xun (Frontiers in Nutrition, 2022)
Pesticide residues are of great significant issue that exerted adverse effects on humans. There is a need for effective and non-toxic decontamination of pesticide residues during food processing. In this minireview, the recent advances in the degradation of pesticide residues by photolysis have been firstly described during food processing. The mechanisms of pesticide residues destruction by photolysis were discussed accordingly. Finally, applications of photolysis in the degradation of pesticide residues were also summarized.